Construction of Saline Creek Tunnel in Athabasca Oil Sand - Chatterji, P. K.; Smith, L. B.; Insley, A. E.; Sharma, L. (Canadian Geotechnical Journal, 1979)
Undisturbed oil sand is very dense and has a relatively high in situ shear strength. However, there is gas present within the oil sand, which causes it to swell once confining pressures are removed, and this results in a significant reduction in the strength of the material. Consequently, this swelling behaviour is a major concern in the design of tunnels in oil sand.Saline Creek Tunnel, located immediately south of the town of Fort McMurray, Alberta, is the first permanent tunnel constructed in the Athabasca Oil Sand. The finished diameter of the tunnel is 4.4 m and the tunnel is about 107 m long of which approximately 73 m is entirely within medium to rich oil sand. The maximum depth of overburden above the tunnel crown is 27.5 m.This paper documents the geotechnical investigation and design of the tunnel. The method of construction and the temporary and permanent tunnel support systems are described. Detailed observations on the behaviour of the oil sand around the tunnel opening during construction are also presented.